Research and Application of Underground Automatic Drilling Rig. Issue 1 (February 2021) - Chen, Xiang; Wang, Song; Yang, Jiangbo; Chen, Fenglei
Abstract: Aiming at the current situation of low automation of underground drilling equipment, an automatic drilling rig which is suitable for underground coal mines has been developed. This paper introduces the layout, parameters, characteristic advantages and the application of the drilling rig. Through the industrial test, the design rationality of the structure of the drilling rig, the reliability of key components for automatic drilling, the reliability of electro-hydraulic control system, and the practicality of automatic drilling function were verified, which reached the expected research and development goals and design requirements, met the technological requirements of automatic drilling in coal mines, enhanced the safety of construction personnel, and reduced the labor intensity.